2019
DOI: 10.2196/13194
|View full text |Cite
|
Sign up to set email alerts
|

Applying a User-Centered Approach to Building a Mobile Personal Health Record App: Development and Usability Study

Abstract: Background A personal health record (PHR) system encourages patients to engage with their own health care by giving them the ability to manage and keep track of their own health data. Of the numerous PHR systems available in the market, many are Web-based patient portals and a few are mobile apps. They have mainly been created by hospitals and electronic health record (EHR) vendors. One major limitation of these hospital-created PHR systems is that patients can only view specific health data extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 49 publications
1
55
0
Order By: Relevance
“…Future research is needed to systematically enrich and prioritise the suggested methods and validate the proposed methodological guidance. [20] Heuristic evaluation with non-users [20,93] Think aloud studies with health care providers [20,88,92], patients [88,92,93] and their relatives [89] Interview [87,89,90] Quantitative surveys with patients [20,37,88,90,91,93] and health care providers [20,87,88], using usability questionnaires…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research is needed to systematically enrich and prioritise the suggested methods and validate the proposed methodological guidance. [20] Heuristic evaluation with non-users [20,93] Think aloud studies with health care providers [20,88,92], patients [88,92,93] and their relatives [89] Interview [87,89,90] Quantitative surveys with patients [20,37,88,90,91,93] and health care providers [20,87,88], using usability questionnaires…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating [8,32,37,38,86,89,93] and adapting [37,91,93] the application in terms of usability and user acceptance under real-life conditions…”
mentioning
confidence: 99%
“…To the best of our knowledge, FirstER is the first mobile app prototype for patients who visit the ED and use their PHRs at other hospitals in an emergency. Whenever patients unintentionally first visited nearby hospitals, FirstER enabled medical personnel to know about the patients' previous underlying diseases, the reasons why they visited other hospitals, and what they were prescribed [17]. Furthermore, we also enabled patients to input their health records (i.e., patient-generated health data), such as conditions and blood pressure results, into FirstER, which then provided physicians with these data to help understand patients' conditions [18].…”
Section: Discussionmentioning
confidence: 99%
“…When perceived ease of use and attitude toward information quality are positive, perceived usefulness is often high [38][39][40]. These findings might help in app design, and developers of an emergency app will need to provide a service that is easy to use, clear and understandable, easy to learn to operate, and easy to navigate and that has clear help messages [41][42][43][44][45].…”
Section: Public Health Implicationsmentioning
confidence: 99%